Entrepreneurship, innovation and consultancy : a practical guide - Saghir, Wael (Routledge, 2026)
This book explores the journey of entrepreneurship, from idea to reality, and outlines the different stages associated with starting an innovative business. As well as being a step-by-step guide to where an idea comes from and how it can be transformed into a business, the book also reviews the practical tools that can be used to harness creativity in entrepreneurial settings.The book is designed to develop general awareness of the entrepreneurial mindset and business start up skills. Taking the reader on a journey from how an idea is incepted, developed and turned into a business, the book shows how to build enterprises and how to find creative and innovative solutions for challenging problems. It aims to introduce readers to the key issues and ideas involved in business start ups, and help them understand the various challenges facing the entrepreneur, as well as how to find and implement creative solutions to these challenges.An essential read for current and aspiring entrepreneurs, business start ups, and students and lecturers on courses in entrepreneurship, business start up and consultancy, Entrepreneurship, Innovation and Consultancy is a vital and practical guide for anyone engaged in starting a new business and who wants to discover more about transforming their business idea into a reality.
Keywords: Business consultants.; Business enterprises -- Technological innovations.; Entrepreneurship.; elektronické knihy; electronic books